Zimbabwe : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2003)
This Selected Issues paper analyzes economic and agricultural developments, and the impact of land reforms of Zimbabwe. The paper summarizes the quantitative estimates of the fiscal burden and overall medium-term macroeconomic impact of HIV/AIDS on Zimbabwe. It reviews the debt restructuring, fiscal sustainability, and the vulnerabilities of Zimbabwe's banking system. It analyzes the situation of major public enterprises and the foreign exchange system in Zimbabwe. It also provides a statistical appendix for Zimbabwe.